Clinical efficacy of haematopoietic stem cell transplantation for adult adrenoleukodystrophy. Issue 1 (14th January 2020) - Matsukawa, Takashi; Yamamoto, Tomotaka; Honda, Akira; Toya, Takashi; Ishiura, Hiroyuki; Mitsui, Jun; Tanaka, Masaki; Hao, Akihito; Shinohara, Akihito; Ogura, Mizuki; Kataoka, Keisuke; Seo, Sachiko; et al.
Abstract: Accumulated experience supports the efficacy of allogenic haematopoietic stem cell transplantation in arresting the progression of childhood-onset cerebral form of adrenoleukodystrophy in early stages. For adulthood-onset cerebral form of adrenoleukodystrophy, however, there have been only a few reports on haematopoietic stem cell transplantation and the clinical efficacy and safety of that for adulthood-onset cerebral form of adrenoleukodystrophy remain to be established. To evaluate the clinical efficacy and safety of haematopoietic stem cell transplantation, we conducted haematopoietic stem cell transplantation on 12 patients with adolescent-/adult-onset cerebral form/cerebello-brainstem form of adrenoleukodystrophy in a single-institution-based prospective study. Through careful prospective follow-up of 45 male adrenoleukodystrophy patients, we aimed to enrol patients with adolescent-/adult-onset cerebral form/cerebello-brainstem form of adrenoleukodystrophy at early stages. Indications for haematopoietic stem cell transplantation included cerebral form of adrenoleukodystrophy or cerebello-brainstem form of adrenoleukodystrophy with Loes scores up to 13, the presence of progressively enlarging white matter lesions and/or lesions with gadolinium enhancement on brain MRI. Clinical outcomes of haematopoietic stem cell transplantation were evaluated by the survival rate as well as by serial evaluation of clinical rating scale scores and neurological and MRI findings. Clinical courses of eight patients who did not undergo haematopoietic stem cell transplantation were also evaluated for comparison of the survival rate. All the patients who underwent haematopoietic stem cell transplantation survived to date with a median follow-up period of 28.6 months (4.2–125.3 months) without fatality. Neurological findings attributable to cerebral/cerebellar/brainstem lesions became stable or partially improved in all the patients. Gadolinium-enhanced brain lesions disappeared or became obscure within 3.5 months and the white matter lesions of MRI became stable or small. The median Loes scores before haematopoietic stem cell transplantation and at the last follow-up visit were 6.0 and 5.25, respectively. Of the eight patients who did not undergo haematopoietic stem cell transplantation, six patients died 69.1 months (median period; range 16.0–104.1 months) after the onset of the cerebral/cerebellar/brainstem lesions, confirming that the survival probability was significantly higher in patients with haematopoietic stem cell transplantation compared with that in patients without haematopoietic stem cell transplantation ( P = 0.0089). The present study showed that haematopoietic stem cell transplantation was conducted safely and arrested the inflammatory demyelination in all the patients with adolescent-/adult-onset cerebral form/cerebello-brainstem form of adrenoleukodystrophy when haematopoietic stem cell transplantation was conducted in the early stages. Further studies are warranted to optimize the procedures of haematopoietic stem cell transplantation for adolescent-/adult-onset cerebral form/cerebello-brainstem form of adrenoleukodystrophy. Abstract : Presently, there are only a few reports on allogenic haematopoietic stem cell transplantation for adult-onset adrenoleukodystrophy. Matsukawa et al. report that survival probability was significantly higher in 12 patients with adolescent-/adult-onset cerebral/cerebello-brainstem form of adrenoleukodystrophy who underwent haematopoietic stem cell transplantation than that in 8 patients who did not undergo haematopoietic stem cell transplantation. Haematopoietic stem cell transplantation arrested the inflammatory demyelination in all the patients. Graphical Abstract: